Screening for suitable mixed microbial consortia from anaerobic sludge and animal dungs for biodegradation of brewery spent grain. (April 2022) - Castilla-Archilla, Juan; Thorn, Camilla E.; Pau, Simone; Lens, Piet N.L.
Abstract: Lignocellulosic wastes, such as brewery spent grain (BSG), represent valuable resources from a biorefinery perspective, being sources of both chemical and energy production. Improving degradation rates of these recalcitrant feedstocks is a necessity, and bioaugmentation with specialised microbial consortia can be a viable means of achieving this. Six sources of mixed microbial consortia were screened, using biodegradation activity tests, for their capacity to enhance production of both chemicals (volatile fatty acids or ethanol) and energy (biogas) from BSG. The inocula used were anaerobic granular sludge as i) intact granules and ii) crushed granules, iii) bovine rumen fluid, and a number of animal manures including iv) giraffe, v) rhinoceros, and vi) tiger. Amplicon sequencing was used to investigate prokaryotic communities within these inocula on day 0 and day 21. Despite herbivore dung harbouring the largest hydrolytic community, the best solids destruction was achieved using anaerobic granular sludge, either intact (64.8 ± 11.9%) or crushed (63.4 ± 3.7% VS destruction). Granular sludge also resulted in the highest gas production, followed by giraffe manure. Contrastingly, the highest volatile fatty acid accumulation was achieved using rhinoceros and tiger manure, at 3.86 (±0.55) and 3.20 (±0.74) gCOD L −1, respectively. Despite these two manure samples having the highest relative abundances of bacteria associated with cellulose and hemicellulose degradation, they supported the poorest solids destruction, perhaps due to the VFA accumulation therein. Thus, while some inocula aided BSG degradation, further research is required to determine the inhibitors of hydrolysis and therefore BSG degradation. Highlights: Six different inocula evaluated for degradation of lignocellulose materials. Highest solid degradation achieved using granular sludge. Highest volatile fatty acid accumulation with rhinoceros and tiger manure.